Journal of Optometry ranks high in Emerging Sources Citation Index (ESCI) - González-Méijome, José Manuel (2021)
[Excerpt] In middle 2021 were published by Clarivate (formerly known as Institute for Science Information –ISI) the Journal Impact Factor (JIF) and the Journal Citation Index (JCI) in Emerging Sources Citation Index (ESCI). In a previous Editorial we discussed some of the different metrics to measure the impact of scientific publication.1 This was further expanded in the recent International Congress of Optometry and Ophthalmic Optics held by the Spanish General Council of Optometrists in Madrid during May 2021.2 In those previous publications we could testify the solid increase of impact for contents published in the Journal of Optometry, and now we can confirm this with the Journal ranking second in the Emerging Sources Citation Index (table 1). It is also interesting to observe that majority of the journals indexed deliver their contents in a 100% Open Access strategy. Looking back 14 years, Journal of Optometry was among the only scientific journals in the field of Visual Science adhering to such publishing scheme. [...]